The Agro-Industrial Complex of the China and the Position of the State in the World Market - V. M. Kuzmina; V. A. Sapryka (Экономика: стратегия и практика)
The PRC is integrated into various economic communities, which allows it to play a significant role in the world market in the production of not only industrial products, but also agricultural ones. The purpose of this article is to analyze the export-import policy and dynamics of mutual trade in agricultural products between the EAEU and China, as well as the capitalization structure of Chinese agro-industrial companies. The article examines the legal basis of the export-import agricultural policy of the PRC, analyzes the dynamics of export-import of agricultural products between the EAEU and China, presents the distribution of Chinese agro-industrial companies by type of business and the distribution of capital of Chinese agro-industrial companies. The study used methods of analysis and synthesis of the studied material based on statistical data from the OECD, the World Bank, the IMF, the UN FAO, FAPRI, as well as the ministries specialized in agriculture of the PRC and the Russian Federation from 2015 to 2022. According to the forecast for 2023, India, China, Africa and a number of Central Asian countries will experience a decrease in world prices for agricultural products. The main conclusion is that China will remain self-sufficient in major crops, although production growth will slow in the coming years